Adrenal Disorders Physiology, Pathophysiology and Treatment (Contemporary Endocrinology,, 2018)
This practical resource provides the latest evidence, management strategies and recommendations for the treatment of disorders of the adrenal glands, including related physiology, genetics and pharmacology. This book is divided into three thematic sections. The first covers adrenal physiology, presenting adrenal zonation and development, the regulation of steroidogenesis, and the pharmacology of glucocortisoids. Part two discusses the genetics and pathophysiology of a number of adrenal disorders, including autoimmune Addison's disease, congenital adrenal hyperplasia, primary aldosteronism, adrenocortical tumors and hyperplasias, and pheochromocytomas and paragangliomas. The final section presents the latest diagnostic and management strategies for these disorders, addressing adrenal insufficiency, adrenal Cushing's Syndrome and aldosteronism, among others. Over the past twenty years, our understanding of disorders of the adrenal glands has been altered and deepened. Providing a much-needed update to the literature, Adrenal Disorders: Physiology, Pathophysiology and Treatment will be an important resource for both academic and clinical endocrinologists working with the adrenal glands and managing patients with adrenal disorders.